Dexmedetomidine Improves Postoperative Patient-Controlled Analgesia following Radical Mastectomy - Fan, Wei; Xue, Hong; Sun, Yong; Yang, HaiKou; Zhang, Jun; Li, Guangming; Zheng, Ying; Liu, Yi (Frontiers in Pharmacology, 2017)
Acute postoperative pain following radical mastectomy is a high risk for prolonged convalescence and potential persistent pain in patients with breast cancer. The present study was designed to observe the effect of intraoperative use of dexmedetomidine on acute postoperative pain following radical mastectomy under general anesthesia. Forty-five patients were enrolled into the study and divided into two groups that were maintained with propofol/remifentanil/Ringer’s solution or propofol/remifentanil/Dexmedetomidine followed by morphine-based patient-controlled analgesia. During the first 24 hours following surgery, patients receiving dexmedetomine had lower NRS pain scores, decreased morphine consumption, longer time to first morphine request as well as a trending decreased incidence of adverse effects when compared to those received Ringer’s solution. In conclusion, the present study finds that intraoperative use of dexmedetomidine could promote analgesic property of postoperative morphine.